Relevance of lung ultrasound in the diagnostic algorithm of respiratory diseases in a real‐life setting: A multicentre prospective study. Issue 5 (2nd August 2019) - Rinaldi, Luca; Milione, Stefania; Fascione, Maria Chiara; Pafundi, Pia Clara; Altruda, Concetta; Di Caterino, Mafalda; Monaco, Lucio; Reginelli, Alfonso; Perrotta, Fabio; Porta, Giovanni; Venafro, Mario; Acierno, Carlo; et al.
ABSTRACT: Background and objective: The aim of this study was to assess the role of lung ultrasound (LUS) in a diagnostic algorithm of respiratory diseases, and to establish the accuracy of LUS compared with chest radiography (CXR). Methods: Over a period of 2 years, 509 consecutive patients admitted for respiratory‐related symptoms to both emergency and general medicine wards were enrolled and evaluated using LUS and CXR. LUS was conducted by expert operators who were blinded to the medical history and laboratory data. Computed tomography (CT) of the chest was performed in case of discordance between the CXR and LUS, suspected lung cancer and an inconclusive diagnosis. Diagnosis made by CT was considered the gold standard. Results: The difference in sensitivity and specificity between LUS and CXR as demonstrated by ROC curve analyses (LUS‐AUROC: 0.853; specificity: 81.6%; sensitivity: 93.9% vs CXR‐AUROC: 0.763; specificity: 57.4%; sensitivity: 96.3%) was significant ( P = 0.001). Final diagnosis included 240 cases (47.2%) of pneumonia, 44 patients with cancer (8.6%), 20 patients with chronic obstructive pulmonary disease (COPD, 3.9%), 24 patients with heart failure (4.7%) and others (6.1%). In 108 patients (21.2%) with any lung pathology, a CT scan was performed with a positive diagnosis in 96 cases (88.9%); we found that CXR and LUS detected no abnormality in 24 (25%) and 5 (5.2%) cases, respectively. LUS was concordant with the final diagnosis ( P < 0.0001), and in healthy patients, there was a low percentage of false positives (5.9%). Conclusion: The results support the routine use of LUS in the clinical context. Abstract : Lung ultrasound (LUS) provided a useful diagnostic workup of respiratory disease, either by directly identifying pathological findings or by detecting indirect signs of illness, as in lung cancer. Overall, LUS was not inferior to chest radiography and routine use in medical wards or in emergency department settings is beneficial. See related Editorial